Cards on the table! Ideas for tackling the EU's constitutional malaise - Daniela Schwarzer; Andreas Maurer (Stiftung Wissenschaft und Politik (SWP), 2006)
The "pause for thought" decreed by the heads of state and government for themselves and their citizens after the voters in France and the Netherlands rejected the Treaty Establishing a Constitution for Europe has been extended for at least another year. The European Council meeting on 15th and 16th June 2006, did little more than sketch out the way forward for the period 2006-2008: by the end of 2008, decisions should have been taken on the question how to continue the reform process. A concrete strategy for implementing the Constitutional Treaty or an alternative treaty, still appears out of reach. Before even beginning to agree on how to move forward, all 25 European Union member states would have to state clearly what goals they are pursuing in the process of institutional reform (a process which all sides agree is necessary) and what steps they believe are required for achieving these goals. In this context, clear statements on the importance of the Treaty and its fate are needed. Consensus on these issues is unlikely to be achieved among all 25 member states. In order to allow a constructive discussion to take place regardless, the 25 would have to agree on shared criteria for assessing the reform proposals that are on the table, and on the options for resolving the "constitutional crisis." (SWP Comments / SWP)
Keywords: 320